Eliciting Implicit Awareness in Alzheimer’s Disease and Mild Cognitive Impairment: A Task-Based Functional MRI Study - Tondelli, Manuela; Benuzzi, Francesca; Ballotta, Daniela; Molinari, Maria Angela; Chiari, Annalisa; Zamboni, Giovanna (Frontiers in Aging Neuroscience, 2022)
Background. Recent models of anosognosia in dementia have suggested the existence of an implicit component of self-awareness abut one’s cognitive impairment that may remain preserved and continue to regulate behavioral, affective, and cognitive responses even in people who do not show explicit awareness of their difficulties. Behavioral studies have used different strategies to demonstrate implicit awareness in patients with anosognosia, but no neuroimaging studies have yet investigated its neural bases. Methods. Patients with amnestic mild cognitive impairment and dementia due to Alzheimer’s Disease underwent functional magnetic resonance imaging during the execution of a colour-naming task in which they were presented with neutral, negative, and dementia-related words (Dementia-Related Emotional Stroop). Results. Twenty-one patients were recruited: 12 were classified as aware and 9 as unaware according to anosognosia scales (based clinical judgement and patient-caregiver discrepancy). Behavioral results showed that aware patients took the longest time to process dementia-related words, although differences between word types were not significant, limiting interpretation of behavioral results. Imaging results showed that patients with preserved explicit awareness had a small positive differential activation of the posterior cingulate cortex (PCC) for the dementia-related words condition compared to the negative words, suggesting attribution of emotional valence to both conditions. PCC differential activation was instead negative in unaware patients, i.e. lower for dementia-related words relative to negative-words. In addition, the more negative the differential activation, the lower was the Stroop effect measuring implicit awareness. Conclusion. PCC preserved response to dementia-related stimuli may be a marker of preserved implicit self-awareness.